PROSES PENGERINGAN JAMUR LINGZHI (GANODERMA LUCIDIUM) MENGGUNAKAN MEDIA UDARA YANG DIDEHUMIDIFKASI OLEH ZEOLIT ALAM - M. Ikhwan Shofarudin; Tri Nugroho; M. Djaeni (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Drying is process that establish the quality of Lingzhi mushrom and then it will influence the price of mushrom. Dryng process which did by farmer of lingshi mushrom use the light of sun which have some weakness, drying time reached 5 days, dependence on season, bigger space need to drying, and operational cost that reach 3 times more expensive in rainy season. The goals of this research are to dry lingzhi mushrom in tray dryer using natural zeolite to make drying process faster, to obtain the effect of operation condition to drying process, and to obtain the effect of operation condition to lingzhi mushrom quality. the condition operation in this research are air temperatures ( 40, 50, 60C), air velocity (6, 8, 10 m/s), and the use of natural zeolite. this research are done by drying lingzhi mushrom in tray dryer during 15 hours until the obtaine the certain moisture content. The result of this research are as follow: at air velocity 8 m/s Nc 400C = 0.0268, Nc 500C = 0.0295, Nc 600C = 0.0297. at temperature 600C obtained Nc at velocity 6 m/s, Nc = 0.0291, at velocity 8 m/s, Nc = 0.0297, and at velocity 10 m/s, Nc = 0.0315, whereas at air velocity 8 m/s with temperature 600C Non zeolite variable Nc = 0.0256, where using of zeolite, Nc = 0.0297. From these data, we can conclude that as the air temperature and air velocity increase, the drying rate will increase therefore drying process takes shorter time. Using of zeolite on drying process make it faster, The best quality of dry lingzhi mushrome with maximum moisture content 12-14% is obtained when using zeolite at air velocity 8 m/s, air temperature 600C also at air velocity 10 m/s at temperature 400C, 500C, and 600C.